RENTANBILITAS PENGGUNAAN DANA HAJI UNTUK INVESTASI INFRASTRUKTUR PADA BADAN PENGELOLA KEUANGAN HAJI (BPKH) - Ikhwani, Aulia; Rozalinda, Rozalinda; Wira, Ahmad (Mabrur: Academic Journal of Hajj and Umra, 2024)
The research is aimed at discussing how the use of Hajj funds for infrastructure investment and to identify implementation of the Hajj Fund investment management. This type of research is normative legal research In the process of data collection, the authors use the method of research library of data sources i.e. legislative regulations, books, official documents, publications, and research results. The results of this research show that no investment of Hajj funds for infrastructure, but in the form of publication of Syari’ah State Valuable Letter (SBSN) in Sukuk Haji Fund Indonesia (SDHI) invested and also carried out in form of banking products, securities, gold, direct investment and other investments. The placement and/or investment of Hajj finances is carried out in accordance with the principles of Shariah, taking into account security, caution, value of benefits, and liquidity.